The environmental performance of torrefied microalgae biomass using torrefaction severity factor - Rivera, Diana Rose T. (Animo Repository, 2019)
Torrefaction is a thermochemical process for upgrading raw biomass into a more energy-dense fuel. However, the production of torrefied microalgae biochar may include environmental impact as it consumes raw materials and energy. In this study, a life cycle assessment study was conducted to understand and assess the corresponding global warming potential associated with the production of torrefied microalgae biomass, using a cradle-to-gate scope. Using different scale models of torrefied microalgae biomass production, this study identifies the contribution of the torrefaction process to the overall environmental impact. Using the experimental data, the study was able to analyze the impact of the torrefaction process on biomass thermal degradation using the torrefaction severity factor. The inclusion of the torrefaction severity factor shows that there was a strong relationship on the resulted global warming potential. It revealed that the influence of the torrefaction temperature was higher as compared to the torrefaction duration.Result of the study shows that the torrefaction process had a minimal contribution of 1-20% to the resulted overall environmental impacts. The overall impact shows that up-scaling production can result in a negative carbon dioxide emission. © 2019 IEEE.